Health and economic consequences of applying the United States' PM2.5 automobile emission standards to other nations: a case study of France and Italy. (June 2020) - Kim, S.; Xiao, C.; Platt, I.; Zafari, Z.; Bellanger, M.; Muennig, P.
Abstract: Objectives: The US has among the world's strictest automobile emission standards, but it is now loosening them. It is unclear where a nation should draw the line between the associated cost burden imposed by regulations and the broader societal benefits associated with having cleaner air. Our study examines the health benefits and cost-effectiveness of introducing stricter vehicle emission standards in France and Italy. Study design: Quasi-experimental study. Methods: We used cost-effectiveness modeling to measure the incremental quality-adjusted life years (QALYs) and cost (Euros) of adopting more stringent US vehicle emission standards for PM2.5 in France and Italy. Results: Adopting Obama era US vehicle emission standards would likely save money and lives for both the French and Italian populations. In France, adopting US emission standards would save €1000 and increase QALYs by 0.04 per capita. In Italy, the stricter standards would save €3000 and increase QALYs by 0.31. The results remain robust in both the sensitivity analysis and probabilistic Monte Carlo simulation model. Conclusions: Adopting more stringent emission standards in France and Italy would save money and lives. Highlights: Adopting Obama era US vehicle emission standards would save money and lives for both the French and Italian populations. In France, adopting US standards would save €1000 and increase quality-adjusted life years (QALYs) by 0.04 per capita. In Italy, the stricter standards would save €3000 and increase QALYs by 0.31. The results remain robust in both the sensitivity analysis and probabilistic Monte Carlo simulation model.